Reconceptualizing Storytelling as Social Constructivist Literacy Practice in Nonformal Education Settings - Desika Putri Mardiani; Tri Lestari; Gunarti Dwi Lestari; Tri ‘Ulya Qodriyati (International Journal of Learning Reformation in Elementary Education, 2026)
The study explores storytelling as a social constructivist literacy practice in a non-formal education setting, specifically within a community library in Surabaya. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving library coordinators, tutors, parents, and children aged 7–12.  Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that storytelling functions as a dialogic literacy space where children actively participate in narrative reconstruction, collaborative meaning-making, and socially mediated interaction. Through expressive storytelling, reflective questioning, and storytelling practices, children demonstrated improvements in reading comprehension, oral communication, confidence, and participation in literacy activities. The study highlights the role of tutors, peer interaction, and family support in shaping a literacy ecosystem that enhances children's reading comprehension, communication skills, and confidence. The research contributes to the conceptual understanding of literacy as a socially mediated and contextually grounded practice in non-formal education.